MOMENTS OF PRIVATE AND LITERARY AND ARTISTIC BROTHERHOOD I.S. TURGENEV AND N.N. TOLSTOY - Tangirova G. I. (Galaxy International Interdisciplinary Research Journal, 2023)
The article considers the moments of creative and friendly relations between the Russian writer I.S. Turgenev and N. N. Tolstoy. Collected together, the letters recreate the atmosphere of family relationships in the Tolstoy family. The atmosphere of love, friendship, devotion and frankness. The correspondence sheds light on some little-known facts from the life of N.N. Tolstoy and I.S. Turgenev. Complements the information about the history of the creation of the work by I.S. Turgenev’s Notes of a Hunter.